The Costs and Benefits of Occupational Healthcare Programmes for UK Firms: An Investigation - Charlton, Michael (2007)
The cost of sickness absence for UK firms is considerable, estimated to be somewhere between ÃÂ£13 and ÃÂ£20 billion (CBI/AXA, 2007). The degree to which individual employers tackle workplace health issues and manage absenteeism varies considerably. Some will engage the services of occupational health providers; others will leave health issues to individual employees and the State. The amount actually spent by employers on occupational healthcare is trivial compared to the cost of absence suggesting that firms do not value or undervalue the contribution of workplace healthcare programmes.